KOMUNIKASI INTERPERSONAL BERBASIS BUDAYA DALAM PEMBENTUKAN EMPATI DAN SOLIDARITAS DIASPORA MADURA DI MALAYSIA - Syukkur Syukkur; Subairi Subairi (STKIP Pesisir Selatan, 2026)
It focuses on how local cultural values shape interpersonal communication patterns that subsequently contribute to the development of social empathy and diaspora solidarity. The research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with eight Madurese migrant informants, participant observation, and documentation conducted in Selangor, Johor, and Penang, Malaysia. The data were analyzed using thematic analysis. The findings indicate that interpersonal communication within the Madurese diaspora is strongly influenced by the cultural value of bhuppa’-bhabhu’-ghuru-rato, which serves as a normative framework guiding social relationships and interactions. This cultural orientation promotes familial, affective, and trust-based communication among community members. As a result, multidimensional social empathy emerges, encompassing cognitive, affective, and conative dimensions. Social empathy is reflected not only in migrants’ understanding of the difficulties and experiences of fellow migrants but also in tangible forms of assistance and mutual support. Furthermore, social empathy functions as a foundation for the formation of diaspora solidarity, which is manifested through informal support networks and collective actions within the migrant community.